Keputusan Pembelian Pada Inovasi Produk Dan Peran Lokasi M2M Indonesian Fast Food Cabang Gedangan-Sidoarjo - RENATA BULAN CAHYONO, NADYA (Jurnal Ilmu Manajemen (JIM), 2019)
The high competition between fast food companies causes each company to realize a need to innovate on products and maximize the choice of business locations for the survival of the company. This study had a purpose to analyze and discuss the influence of product innovation and location on the decision to purchase the M2M Indonesian Fast Food product innovation at the Gedangan-Sidoarjo branch. Non-probability sampling used as sampling technique with judgmental sampling method on 220 respondents. The respondents are consumers who have already bought, who made their own decisions in purchasing, and consumed one of the products of ayam geprek, ayam super pedas, chicken keju, and chicken teriyaki M2M Indonesian Fast Food Gedangan-Sidoarjo branch at age 21-50 year. Likert scale used as measurement scale. Questionnaire used as the measuring instrument. Multiple linear regression equation models used as data analysis. The results showed product innovation had a positive influence on decision to purchase, and location had a positive influence on decision to purchase. Keywords: franchise; fast food; location; product innovation; purchase decision